Human suffering needs the ‘face’ and ‘eyes’ of God. Perspectives on Psalm 13 - Human, Dirk (Old Testament Essays, 2021)
The COVID-19 global pandemic and its consequent outcomes have caused immense suffering and distress in every community and at all levels of life worldwide. Theological and religious communities raise the question about God’s involvement in the causes of and healing from this horrendous misery and grief. These questions become paradigmatic of how God is involved in suffering and how the supplicant could experience deliverance through interaction with God, whilst situated in the midst of such a crisis. Exegetic contemplation on Ps 13, a well-known lament song, provides an exemplary experience of a psalmist in a severe life-endangering context. An exposition of the text—its historical, cultic and literary contexts—and the genre of ‘lament’ brings insight into the Yahweh-believer’s interaction. Without pretending to provide answers to enigmatic forms of suffering, this article shows how Yahweh-believers in ancient Israel understood and reacted to suffering. Human suffering is indeed in need of the ‘face’ and ‘eyes’ of Yahweh to experience healing and redemption. https://doi.org/10.17159/2312–3621/2021/v34n1a15